PERENCANAAN BISNIS PADA UMKM VEZARA COLLECTION - Yusbardini; Marcello; Cahyadi, Said Ashadi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
The purpose of this service is to provide training in creating business plans for novice entrepreneurs. A business plan is a written document that outlines the external and internal elements involved in starting a new business. Typically, a business plan includes the company's main objectives and strategies. However, many MSMEs (Micro, Small, and Medium Enterprises) face challenges due to limited human resources with expertise in this area. As a result, their business plans are often created based on immediate needs rather than being thoroughly developed. Consequently, business owners, especially young entrepreneurs like Mrs. Desy, may encounter difficulties in the future as they run their businesses. To address this issue, the PKM Team aims to provide training on how to create a comprehensive business plan, offering valuable support to Mrs. Desy and other entrepreneurs in PGC. A well-crafted business plan is essential for achieving success in business ventures.